Loss of enhancer of zeste homologue 2 (EZH2) at tumor invasion front is correlated with higher aggressiveness in colorectal cancer cells - Böhm, Julian; Muenzner, Julienne Kathrin; Caliskan, Aylin; Ndreshkjana, Benardina; Erlenbach-Wünsch, Katharina; Merkel, Susanne; Croner, Roland; Rau, Tilman; Geppert, Carol-Immanuel; Hartmann, Arndt; Roehe, Adriana Vial; Schneider-Stock, Regine (Journal of Cancer Research and Clinical Oncology, 2019)
Purpose: Enhancer of zeste homolog 2 (EZH2) is associated with epigenetic gene silencing and aggressiveness in many tumor types. However, the prognostic impact of high EZH2 expression is controversially discussed for colorectal cancer. For this reason, we immunohistochemically analyzed EZH2 expression in 105 specimens from colon cancer patients separately for tumor center and invasion front. Methods: All sections from tissue microarrays were evaluated manually and digitally using Definiens Tissue Studio software (TSS). To mirror-image the EZH2 status at the tumor invasion front, we treated HCT116 colon cancer cells with the EZH2 inhibitor 3-Deazaneplanocin A (DZNep) and studied the growth of in ovo xenografts in the chorioallantoic membrane (CAM) assay. Results: We showed a significant decrease in EZH2 expression and the repressive H3K27me3 code at the tumor invasion front as supported by the TSS-constructed heatmaps. Loss of EZH2 at tumor invasion front, but not in tumor center was correlated with unfavorable prognosis and more advanced tumor stages. The observed cell cycle arrest in vitro and in vivo was associated with higher tumor aggressiveness. Xenografts formed by DZNep-treated HCT116 cells showed loosely packed tumor masses, infiltrative growth into the CAM, and high vessel density. Conclusion: The differences in EZH2 expression between tumor center and invasion front as well as different scoring and cutoff values can most likely explain controversial literature data concerning the prognostic value of EZH2. Epigenetic therapies using EZH2 inhibitors have to be carefully evaluated for each specific tumor type, since alterations in cell differentiation might lead to unfavorable results.
CRIS-Team Scopus Importer:2019-07-23
Keywords: CAM assay; Colorectal cancer; EZH2; EZH2 inhibition; Tumor invasion front; Worse prognosis